Analisis Pengaruh Produk, Harga, Promosi Dan Tempat Pemasaran Terhadap Keputusan Pelanggan Cafe Teraswara Sidodadi Kabupaten Labuhanbatu Selatan Serta Makanan Halal Sebagai Variabel Moderating - Hendra Lesmana (Universitas Labuhanbatu, 2021)
This study aims to examine the analysis of the influence of products, prices, promotions and marketing places on customer decisions Cafe Teraswara Sidodadi South Labuhanbatu and Halal food as a Moderating variable. Data collection was carried out by distributing questionnaires and distributed to 70 research samples, namely Cafe teraswara consumers. Data analysis in this study using the help of SPSS version 20. Data testing techniques conducted in this study include validity and reliability test, classical assumption test, multiple linear regression analysis, and partial and simultaneous testing. The results of the analysis showed that the product has a positive effect on purchasing decisions moderated by halal food it can be seen from the value of t count > t table (6,530>1,997), the price has a positive effect on purchasing decisions moderated by halal food it can be seen from the value of t count > t table (3,387>1,997), promotion has a positive effect on purchasing decisions moderated by halal food it can be seen from the value of t count > t table (3,695>1,997), marketing places have a positive effect on purchasing decisions moderated by halal food this can be seen from the value of t count > t table (3.651>1.997), products, prices, promotions and marketing places have a positive effect on purchasing decisions moderated by halal food this can be seen from the value of F count > F table (97.562>2.51).